Preaching to the Agnostic: Inflation Reporting Can Increase Trust in the Central Bank but Only among People with Weak Priors - Bernd Hayo; Pierre-Guillaume Méon (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using a randomized controlled trial, we study whether showing German respondents a graph plotting the European Central Bank's inflation target alongside inflation in the euro area from 1999 to 2017 affects respondents' trust in the ECB. The treatment has, on average, no significant effect on the level of trust in the ECB respondents report, but trust increases among respondents who report no preference for any political party. Within this group, the information about the actual development of the inflation rate, and not information about the inflation target itself, appears to be the main driving force.
Keywords: E52; E58; Z10; 330; central bank trust; European Central Bank; central bank communication; monetary policy; Germany; household survey; RCT